1991
DOI: 10.1111/j.1365-2133.1991.tb03281.x
|View full text |Cite
|
Sign up to set email alerts
|

"High single-dose' European PUVA regimen also causes an excess of non-melanoma skin cancer

Abstract: We report the results of a long-term (12.8 years) follow-up study of the detection of malignant and benign skin tumours in patients with psoriasis, who were treated with PUVA according to the European, 'high single-dose' regimen. A total of 13 squamous cell carcinomas (SCC) and 24 basal cell carcinomas (BCC) were diagnosed in 11 of 260 patients. The incidence of both SCC and BCC was increased in comparison with the general Dutch population. The ratio of SCC to BCC in the general population was 1:8 but was 1:2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 16 publications
2
75
0
5
Order By: Relevance
“…To prevent recurrences PUVA therapy is usually administered on a long-term basis. However, several studies have demonstrated that high-dose exposure to PUVA increases significantly the risk of the development of squamous-cell carcinoma (SCC) [2, 3, 4, 5, 6]. Although initially large-scale European studies, in contrast to US studies, did not reveal an increased risk of SCC unless the patient belonged to the risk group with prior exposure to other potential carcinogens, a positive correlation has been found lately [7].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent recurrences PUVA therapy is usually administered on a long-term basis. However, several studies have demonstrated that high-dose exposure to PUVA increases significantly the risk of the development of squamous-cell carcinoma (SCC) [2, 3, 4, 5, 6]. Although initially large-scale European studies, in contrast to US studies, did not reveal an increased risk of SCC unless the patient belonged to the risk group with prior exposure to other potential carcinogens, a positive correlation has been found lately [7].…”
Section: Introductionmentioning
confidence: 99%
“…In primates receiving 2-18 mg kg-' 8-MOP orally, only dosedependent emesis, but no organ damage was observed [20]. Chronic surveillance of PUVA therapy has failed to identify any clinically relevant toxicity [16,21]. Also, a prospective study over 5 years examining ophthalmological findings in patients receiving PUVA indicated a small risk of ocular damage in patients who received at least 100 PUVA treatments [22].…”
Section: Pharmacokinetic Analysis Linearity Analysis Figures 1 and 2 mentioning
confidence: 99%
“…Other tumors of lower incidences, including basal cell carcinomas and melanomas, have been reported (Stern et al, 1984;Bruynzeel et al, 1991;Stern et al, 1997Stern and Lunder, 1998;McGinnis et al, 2003). The International Agency for Research on Cancer (IARC) has classified PUVA as a group I carcinogen (IARC, 1980(IARC, , 1987.…”
Section: Introductionmentioning
confidence: 97%